في شروط اللا تسامح - والاعتدال المانع للتطرف وإرهابه - عبيس, رائد; مظلوم, رملة خضير (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
In this research entitled (On the Conditions of Intolerance and Moderation that Prevent Extremism and Its Terrorism), we talked about a number of types of intolerance that crystallize in the behaviors of individuals and groups in various and numerous ways and methods. We mentioned in this study a number of types of intolerance that oppose moderation and help in the growth of extremism and its terrorism in the form of individual motives or projects of rule, domination, control and politics, as Al-Qaeda and ISIS did in Iraq and the region. We reviewed these types with explanation and comparison with what helps in their growth and alerting them societally and individually amidst factors that enhance the growth of these intolerant behaviors in various societal circles, whether official or social. Which became clear from them are long-term motives in various political, military, colonial and economic employments. It began to work against rational efforts that push for the dissemination of a culture of moderation, acceptance and peaceful coexistence among members of one society and neighboring societies regionally and even internationally within the international peace projects called for by moderate and tolerant social circles to the extent that they preserve security, safety, dignity and rights. The goal is completed by the proposed projects and initiatives in a culture of peace and moderation, through awareness of the dangers of intolerance, intemperance and crisis-ridden extremism that arise from multidimensional psychological motives. As well as sound rational education that rejects the thought of extremism and intolerance of others, as well as religious education based on the principles of love, acceptance and respect for others. The most important thing is teaching tolerant human values that must prevail among human beings.